Sirach, scrolls, and sages : proceedings of a Second International Symposium on the Hebrew of the Dead Sea Scrolls, Ben Sira, and the Mishnah, held at Leiden University, 15-17 December 1997 - Muraoka, T.; Elwolde, J. F. (Studies on the Texts of the Desert of Judah, 1999)
Following a successful symposium held in Leiden in 1995 a second international gathering took place, also in Leiden, two years later. The volume contains revised papers covering a wide range of linguistic and textual subjects and presented by scholars from eight countries: Austria (Reiterer), Denmark (Ehrensvärd), France (Joosten), Israel (Fassberg, Hurvitz, Kister, Qimron), Netherlands (Baasten, Beentjes, Muraoka, van Peursen, van Uchelen, Wesselius), Spain (Pérez Fernández), UK (Aitken, Elwolde), USA (M. Smith). A subject index and an index locorum are included.